Factores sociodemográficos y requisitos de autocuidado en adultos mayores - Marchena Castillo, Ana Claudia (2019)
This research work is a quantitative descriptive correlational study, which is crosssectional type. This study was conducted during the months of May to July 2019 with elderly adults who attended the Senior´s Adult Centre in La Esperanza district, with the objective of determining the relationship between socio-demographic factors: age and sex, and compliance with self-care requirements. The sample consisted of 65 older adults selected according to the inclusion criteria and for the data collection, the Self-Care Requirements Scale (ERA) instrument was used, which were analyzed with the IBM SPSS Statistics 23 software. Finding that 56.9% were young adults (60-74 years old) and 62.2% female. The statistical analysis was performed with the statistical test "Chi square" in Pearson's correlation and it is concluded that if there is a statistically significant relationship between Sex and Compliance with Self-Care Requirements (p < 0.05) and not of this with age (p > 0.05).